Media and Sexism: An Analysis of Changing Trends in Indian Commercial Advertisements and Malayalam Soap Operas - Krishnan, Reshma; B. , Sonia Chellirian (International Journal of Psychosocial Rehabilitation, 2020)
Visual media’s role in forming ideologies in the minds of humans is quite inexplicable. In the Indian context, for every class of Indian society, the most commonly found entertainment is television. As a medium, television has a large audience, and therefore it has a profound influence on the people. Soap operas and the commercial advertisements that come in between are things that the Indian audience is used to. On a close observation, one can see that from time immemorial, both these visual platforms have been highly sexist in their content. Gender stereotyping has become an essential element employed in these operas and advertisements, which in turn feeds the patriarchal values and middle-class morality of Indian society. This makes people glued to their seats, especially during prime time, when the majority seeks television as a way of relaxation. But recently it has been observed that drastic changes are coming in this media. Thought-provoking and realistic commercial advertisements are being made and publicized, and makers of television operas have also started experimenting with fresh and novel subject matter, even though they are fewer in number. The paper will be concentrating on some prominent advertisements and Malayalam television serials for their sexist content, mainly focusing on the changes that have come across in the theme and matter in both the fields. The paper will also be mentioning some old advertisements and serials with their themes critically explored along with the new ones so that it will be more like a comparative study rather than a vague description.